Identification and antibiotic susceptibility of Escherichia coli isolated from chicken samples collected from wet markets in Dhaka city - Chowdhury, Afrida Tasnim; Zarin, Ishrat Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.